2022
DOI: 10.3390/ijms23137434
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib Eliminates Persistent Chlamydia trachomatis Infection through Rapid and Specific Host Cell Apoptosis

Abstract: Chlamydia trachomatis, a parasitic intracellular bacterium, is a major human pathogen that causes millions of trachoma, sexually transmitted infections, and pneumonia cases worldwide. Previously, peptidomimetic inhibitors consisting of a hydrophobic dipeptide derivative exhibited significant inhibitory effects against chlamydial growth. Based on this finding, this study showed that both bortezomib (BTZ) and ixazomib (IXA), anticancer drugs characterized by proteasome inhibitors, have intensive inhibitory activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Drug repurposing, which has been researched mostly in cancer treatment, has also been tried in this regard. Itoh et al have shown that Bortezomib, an anticancer drug, may also be effective in treating CT infection through the induction of apoptosis [100]. More comprehensive studies are needed to be able to apply all these new strategies in the treatment of CT infection and to put the results of research into clinical practice.…”
Section: Treatment Failure and Novel Approachesmentioning
confidence: 99%
“…Drug repurposing, which has been researched mostly in cancer treatment, has also been tried in this regard. Itoh et al have shown that Bortezomib, an anticancer drug, may also be effective in treating CT infection through the induction of apoptosis [100]. More comprehensive studies are needed to be able to apply all these new strategies in the treatment of CT infection and to put the results of research into clinical practice.…”
Section: Treatment Failure and Novel Approachesmentioning
confidence: 99%
“…As for NG infections, the new window of opportunity for treating CT infections includes new drug development, specifically non-antibiotic therapy, or the drug repurposing strategy as an alternative, to "save time" [98]. Recently, some authors have published interesting findings suggesting the use of 4EpDN cyclic peptomer as a prophylactic CT treatment [99].…”
Section: Challenges and Opportunities Of The Current Therapeutic Weaponsmentioning
confidence: 99%
“…Interestingly, drug repurposing, a strategy commonly investigated for cancer treatment, has also been explored in this field [ 99 , 100 ]. Specifically, Itoh et al have reported the potential role of bortezomib, an anticancer drug, to treat Ct infections by apoptosis induction [ 100 ].…”
Section: Treatment Failure and Novel Approachesmentioning
confidence: 99%
“…Interestingly, drug repurposing, a strategy commonly investigated for cancer treatment, has also been explored in this field [ 99 , 100 ]. Specifically, Itoh et al have reported the potential role of bortezomib, an anticancer drug, to treat Ct infections by apoptosis induction [ 100 ]. Notwithstanding all these new strategies for treating Ct infection, further comprehensive studies are needed in order to improve the translation of these research results into clinical practice.…”
Section: Treatment Failure and Novel Approachesmentioning
confidence: 99%